On humans and wildlife in Mediterranean islands - Blondel, Jacques (Journal of Biogeography, 2008)
Aim To investigate the effects of human-induced landscape changes in Mediterranean islands on the ecological and evolutionary responses of bird communities and populations. The combination of mass extinction of large mammals and massive deforestation by humans was hypothesized to produce new selection regimes to which organisms were likely to respond. Habitat selection and niche breadth have been investigated at the scale of species, and phenotypic variation at the scale of local populations. Location The study was carried out along habitat gradients and in habitat mosaics at different spatial scales on the island of Corsica and in areas of similar size and structure in continental France. Methods Two sets of gradients have been used for investigating habitat selection and niche breadth: gradients of altitude, and gradients of vegetation structure. Population studies focused on the blue tit, Cyanistes caeruleus. Large samples of breeding attempts by this species in 10 habitats provided detailed data on phenotypic variation of fitness-related traits both on Corsica and on the mainland. Results The extent of niche space used by birds differed substantially depending on which habitat gradient was considered. Many species have been found to contract their habitat niche along the elevation gradient on Corsica compared with the mainland, whereas all species in the vegetation gradient broadened their niche on the island. Breeding patterns of the blue tit differed considerably depending on whether they settle in deciduous oaks (Quercus humilis) or in evergreen sclerophyllous oaks (Quercus ilex). Phenotypic variation of breeding traits was much higher on the island, where more populations were correctly timed for the best breeding period than on the mainland, a pattern that is likely to result from lower dispersal of organisms on the island. Main conclusions The differences in observed niche breadth between the two series of habitat gradients is explained both by the species-specific ecology of the species and the human-induced environmental history of Corsica. Large-scale landscape changes provided new opportunities for island colonization by non-forest species, which are isolated as small, ‘fugitive’ local populations. In both gradients, forest species that are typical components of the Corsican bird fauna definitely expanded their niche and occupied a wider range of habitats on Corsica than on the mainland. At the population scale, landscapes included habitat patches with contrasted selection regimes, which resulted in high phenotypic variation for many fitness-related traits. Reduced dispersal of birds on the island resulted in a much higher degree of local differentiation on Corsica than on the mainland.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Blue tit; gene flow; habitat gradient; Human disturbance; insular syndrome; landscape changes; local differentiation; mass extinction; niche breadth; phenotypic variation

On humans and wildlife in Mediterranean islands - Blondel, Jacques (Journal of Biogeography, 2008)
Aim To investigate the effects of human-induced landscape changes in Mediterranean islands on the ecological and evolutionary responses of bird communities and populations. The combination of mass extinction of large mammals and massive deforestation by humans was hypothesized to produce new selection regimes to which organisms were likely to respond. Habitat selection and niche breadth have been investigated at the scale of species, and phenotypic variation at the scale of local populations. Location The study was carried out along habitat gradients and in habitat mosaics at different spatial scales on the island of Corsica and in areas of similar size and structure in continental France. Methods Two sets of gradients have been used for investigating habitat selection and niche breadth: gradients of altitude, and gradients of vegetation structure. Population studies focused on the blue tit, Cyanistes caeruleus. Large samples of breeding attempts by this species in 10 habitats provided detailed data on phenotypic variation of fitness-related traits both on Corsica and on the mainland. Results The extent of niche space used by birds differed substantially depending on which habitat gradient was considered. Many species have been found to contract their habitat niche along the elevation gradient on Corsica compared with the mainland, whereas all species in the vegetation gradient broadened their niche on the island. Breeding patterns of the blue tit differed considerably depending on whether they settle in deciduous oaks (Quercus humilis) or in evergreen sclerophyllous oaks (Quercus ilex). Phenotypic variation of breeding traits was much higher on the island, where more populations were correctly timed for the best breeding period than on the mainland, a pattern that is likely to result from lower dispersal of organisms on the island. Main conclusions The differences in observed niche breadth between the two series of habitat gradients is explained both by the species-specific ecology of the species and the human-induced environmental history of Corsica. Large-scale landscape changes provided new opportunities for island colonization by non-forest species, which are isolated as small, ‘fugitive’ local populations. In both gradients, forest species that are typical components of the Corsican bird fauna definitely expanded their niche and occupied a wider range of habitats on Corsica than on the mainland. At the population scale, landscapes included habitat patches with contrasted selection regimes, which resulted in high phenotypic variation for many fitness-related traits. Reduced dispersal of birds on the island resulted in a much higher degree of local differentiation on Corsica than on the mainland.
Keywords: Blue tit; gene flow; habitat gradient; Human disturbance; insular syndrome; landscape changes; local differentiation; mass extinction; niche breadth; phenotypic variation